2008
DOI: 10.1111/j.1399-6576.2008.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fentanyl on gastric myoelectrical activity: a possible association with polymorphisms of the μ‐opioid receptor gene?

Abstract: Fentanyl inhibited gastric myoelectrical activity in about half of the subjects. The variation could not be explained by SNP in the MOR gene. Because of small sample size, the results must be regarded as preliminary observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…However, they found that the incidence of nausea and vomiting was higher in patients with inhibit gastric motility. This finding provides another explanation for postoperative nausea and vomiting, namely this may be associated with the opioid-induced changes in gastric motility [22].…”
Section: Discussionmentioning
confidence: 68%
“…However, they found that the incidence of nausea and vomiting was higher in patients with inhibit gastric motility. This finding provides another explanation for postoperative nausea and vomiting, namely this may be associated with the opioid-induced changes in gastric motility [22].…”
Section: Discussionmentioning
confidence: 68%
“…These anesthetic conditions are not known to affect slow waves, 22,25 except for the use of opiates, which may be associated with myoelectrical abnormalities. 26 …”
Section: Methodsmentioning
confidence: 99%
“…demonstrated no difference in manometric measurements performed, in patients who needed esophageal manometry with and without sedation (1). Several studies have investigated the influence of fentanyl on gastric and duodenal motility in animals (14, 15) and humans (16) However, the results of studies can not be applied directly to esophageal motility due to distinctive differences in motility patterns between these parts of the GI tract. The effects of fentanyl on esophageal motility have not been studied, but its short duration of action makes this drug attractive to use during this type of procedure.…”
Section: Discussionmentioning
confidence: 99%